Effects of lactic, malic and fumaric acids on Salmonella spp. counts and on chicken meat quality and sensory characteristics - Fernandez, Mariano Manuel; Rodriguez, Anabel; Fulco, Micaela; Soteras, Trinidad; Mozgovoj, Marina Valeria; Cap, Mariana (2021)
The aim of this work was to assess the effectiveness of dipping chicken breast in lactic, malic and fumaric acid 3% solutions for 15 s on Salmonella counts, as well as on chicken meat quality and sensory characteristics. All three treatments effectively reduced Salmonella counts. The values of Salmonella log reduction were 2.22, 1.55 and 1.30 log CFU/g for fumaric, malic and lactic treatments, respectively. Although fumaric acid was the most effective for reducing Salmonella counts, chicken meat quality and sensory characteristics were significantly affected, even in cooked samples. Conversely, malic and lactic acids treatments caused minimal changes in chicken meat quality and sensory characteristics compared to control samples. This study shows effective alternatives to reduce Salmonella contamination on chicken breast fillets, although further studies should be considered to improve the effects on quality and sensory attributes.